A graphene quantum dot (GQD) nanosystem with redox-triggered cleavable PEG shell facilitating selective activation of the photosensitiser for photodynamic therapy. Issue 8 (15th January 2016) - Li, Yan; Wu, Zhiyong; Du, Dou; Dong, Haiqing; Shi, Donglu; Li, Yongyong
Abstract : A graphene quantum dot nanosystem with redox-triggered cleavable PEG shell was developed to achieve selective activation of the photosensitiser in tumor-relevant conditions. Abstract : In photodynamic therapy (PDT), selective activation of the photosensitiser in tumor-relevant conditions is highly desirable to avoid side effects. In this study, a graphene quantum dot (GQD) nanosystem, composed of a redox-triggered cleavable PEG shell, was designed and developed for selective recovery of photoactive chlorine e6 (Ce6) in tumor-relevant conditions. In this unique system, the planar π conjugated structure of GQD enables efficient quenching of the photochemical properties of Ce6 in terms of fluorescence and singlet oxygen generation. Once exposed to tumor relevant glutathione (GSH), the disulfide-linked PEG shell undergoes reductive cleavage and subsequent detachment from the GQD scaffold, leading to accelerated release of Ce6 with recovered photoactivity. MTT study against HeLa cells demonstrated the high PDT efficacy of Ce6, regulated by elevated GSH concentration. The studies on in vivo / ex vivo imaging and photodynamic efficacy demonstrated superior biocompatibility of the GQD nanosystem compared with the widely reported graphene oxide (GO)-based nanovehicle. Intravenously injected GQD–SS–PEG/Ce6 showed effective suppression of tumor growth.